I'd give anything : a novel - De los Santos, Marisa, 1966- (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"Ginny Beale is eighteen, irreverent, funny, and brave, with a brother she adores and a circle of friends for whom she would do anything. Because of one terrible night, she loses them all, and her adventurous spirit, seemingly forever. While the town cheers on the high school football team, someone sets the school's auditorium ablaze. Ginny's best friend Gray Marsden's father, a fire fighter, dies in the blaze. While many in the town believe a notoriously troubled local teen set the fire, Ginny makes a shattering discovery that casts blame on the person she trusts most in the world. Ginny tells no one, but the secret isolates her, looming between her and her friends and ruining their friendship."--Publisher description.